Epilepsy in Rett syndrome—Lessons from the Rett networked database. (19th March 2015) - Nissenkorn, Andreea; Levy‐Drummer, Rachel S.; Bondi, Ori; Renieri, Alessandra; Villard, Laurent; Mari, Francesca; Mencarelli, Maria A.; Lo Rizzo, Caterina; Meloni, Ilaria; Pineda, Mercedes; Armstrong, Judith; Clarke, Angus; et al.
Summary Objective Rett syndrome is an X‐linked dominant neurodevelopmental disorder caused by mutations in the MECP2 gene, and characterized by cognitive and communicative regression, loss of hand use, and midline hand stereotypies. Epilepsy is a core symptom, but literature is controversial regarding genotype–phenotype correlation. Analysis of data from a large cohort should overcome this shortcoming. Methods Data from the Rett Syndrome Networked Database on 1, 248 female patients were included. Data on phenotypic and genotypic parameters, age of onset, severity of epilepsy, and type of seizures were collected. Statistical analysis was done using the IBM SPSS Version 21 software, logistic regression, and Kaplan‐Meier survival curves. Results Epilepsy was present in 68.1% of the patients, with uncontrolled seizures in 32.6% of the patients with epilepsy. Mean age of onset of epilepsy was 4.68 ± (standard deviation) 3.5 years. Younger age of onset was correlated to severity of epilepsy (Spearman correlation r = 0.668, p < 0.01). Patients with late truncating deletions had lower prevalence of epilepsy. Compared to them, the p.R133C mutation, associated with a milder Rett phenotype, increased the risk for epilepsy (odds ratio [OR] 2.46, confidence interval [CI] 95% 1.3–4.66), but not for severe epilepsy. The p.R255X mutation conferred an increased risk for epilepsy (OR 2.07, CI 95% 1.2–3.59) as well as for severe epilepsy (OR 3.4, CI 95% 1.6–7.3). The p.T158M and p.C306C mutations relatively increased the risk for severe epilepsy (OR 3.09 and 2.69, CI 95% 1.48–6.4 and 1.19–6.05, respectively), but not for epilepsy occurrence. Significance Various mutations in the MECP2 gene have a different influence on epilepsy, unrelated to the severity of the general Rett phenotype. This might suggest a site‐specific effect of MeCp2 on epileptic pathways. Further investigation of these mechanisms should promote better understanding of epileptogenesis in Rett syndrome.